New cobalt hydroxycarbonate-based material for highly sensitive enzyme-free glucose sensors - Zh. K. Kalkozova; L. V. Gritsenko; U. A. Balgimbayeva; M. T. Gabdullin; Dan Wen; Kh. A. Abdullin (Scientific Reports)
Abstract Health monitoring with glucose sensors is essential for preventing various diseases and maintaining overall well-being. Among the numerous analytical methods used to measure glucose levels, electrochemical enzyme-free methods show high practical potential. Developing new materials for highly sensitive and stable enzyme-free sensors is of significant importance. This study presents hydroxycarbonates as a new class of materials for creating enzyme-free glucose sensors and demonstrates, for the first time, that nanostructured cobalt hydroxycarbonate is a promising candidate for effective sensor applications. Prepared using a simple one-step hydrothermal method, this material exhibited a sensitivity of 1950 µA cm−2 mM−1 with a detection limit (LOD) of approximately 30 µM and a linear range up to 3 mM glucose. In addition, the sensitivity of the sensor synthesized in a 0.1 M cobalt nitrate solution was found to increase by more than 3 times up to 6745 µA cm−2 mM−1 when only 2 mol% of zinc nitrate was added to the growth solution containing cobalt nitrate and urea during synthesis. This adjustment also significantly affects the lattice vibration spectrum and material morphology, reducing the average nanoparticle size from 30 nm to 7–8 nm. The sensors demonstrated high long-term stability when stored under normal conditions. These results highlight the significant potential of the new sensor material for the quantitative detection of glucose.